Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Complex carbon cycle responses to multi‐level warming and supplemental summer rain in the high A rctic - Elizabeth D. Sharp; Patrick F. Sullivan; Heidi Steltzer; Adam Z. Csank; Jeffrey M. Welker (Global Change Biology, 2013)
The Arctic has experienced rapid warming and, although there are uncertainties, increases in precipitation are projected to accompany future warming. Climate changes are expected to affect magnitudes of gross ecosystem photosynthesis ( GEP ), ecosystem respiration ( ER ) and the net ecosystem exchange of CO 2 ( NEE ). Furthermore, ecosystem responses to climate change are likely to be characterized by nonlinearities, thresholds and interactions among system components and the driving variables. These complex interactions increase the difficulty of predicting responses to climate change and necessitate the use of manipulative experiments. In 2003, we established a long‐term, multi‐level and multi‐factor climate change experiment in a polar semidesert in northwest G reenland. Two levels of heating (30 and 60 W m −2 ) were applied and the higher level was combined with supplemental summer rain. We made plot‐level measurements of CO 2 exchange, plant community composition, foliar nitrogen concentrations, leaf δ 13 C and NDVI to examine responses to our treatments at ecosystem‐ and leaf‐levels. We confronted simple models of GEP and ER with our data to test hypotheses regarding key drivers of CO 2 exchange and to estimate growing season CO 2 ‐C budgets. Low‐level warming increased the magnitude of the ecosystem C sink. Meanwhile, high‐level warming made the ecosystem a source of C to the atmosphere. When high‐level warming was combined with increased summer rain, the ecosystem became a C sink of magnitude similar to that observed under low‐level warming. Competition among our ER models revealed the importance of soil moisture as a driving variable, likely through its effects on microbial activity and nutrient cycling. Measurements of community composition and proxies for leaf‐level physiology suggest GEP responses largely reflect changes in leaf area of S alix arctica , rather than changes in leaf‐level physiology. Our findings indicate that the sign and magnitude of the future High A rctic C budget may depend upon changes in summer rain.

Deep Autotrophic Soil Respiration in Shrubland and Woodland Ecosystems in Central New Mexico - D. O. Breecker; L. D. McFadden; Z. D. Sharp; M. Martinez; M. E. Litvak (Ecosystems, 2012)

Fluid migration through thrust faults in the Helvetic nappes (Western Swiss Alps) - D. L. Kirschner; H. Masson; Z. D. Sharp (Contributions to Mineralogy and Petrology, 1999)